2022
DOI: 10.26714/magnamed.9.1.2022.51-61
|View full text |Cite
|
Sign up to set email alerts
|

Co-Existence of Tuberculosis and Lung Cancer

Abstract: Background: Tuberculosis (TB) and lung cancer cause significant morbidity and mortality worldwide and pose a global health threat. Each year these two diseases account for more than 1.6 million deaths worldwide. The incidence of both diseases is still high in many developing countries, especially in Asian countries. TB and lung cancer are often confused and misdiagnosed, especially in countries with diagnostic challenges of low TB incidence and risk of missed diagnosis.Case Presentation: The following is a cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The prevalence of TB coexistence with malignancy remains unknown. Compared to a previous study by Cicenas et al [8], an investigation in Turkey also showed a higher prevalence of TB coexistence with lung malignancy cases, which was approximately 4% [7,8].…”
Section: Case Presentationcontrasting
confidence: 62%
See 1 more Smart Citation
“…The prevalence of TB coexistence with malignancy remains unknown. Compared to a previous study by Cicenas et al [8], an investigation in Turkey also showed a higher prevalence of TB coexistence with lung malignancy cases, which was approximately 4% [7,8].…”
Section: Case Presentationcontrasting
confidence: 62%
“…The coexistence between TB and malignancy, specifically sarcoma, remains uncertain. Cicenas et al [8] reported that 2.1% of TB cases were accompanied by lung malignancy in Lithuania from 1990 to 2015 [7,8]. The coexistence between lung carcinoma and TB was simultaneously reported to be around 2% and was observed in the upper lobe [9].…”
Section: Case Report D E a P U T R I A U D I N A E T A Lmentioning
confidence: 99%